Evolution of an ancient (Lower Cretaceous) marginal‐marine system from tide‐dominated to wave‐dominated deposition, McMurray Formation. Issue 6 (5th June 2019) - Weleschuk, Zennon P.; Dashtgard, Shahin E.
Abstract: Regionally extensive parasequences in the upper McMurray Formation, Grouse Paleovalley, north‐east Alberta, Canada, preserve a shift in depositional processes in a paralic environment from tide domination, with notable fluvial influence, through to wave domination. Three stacked parasequences form the upper McMurray Formation and are separated by allogenic flooding surfaces. Sediments within the three parasequences are grouped into three facies associations: wave‐dominated/storm‐dominated deltas, storm‐affected shorefaces to sheltered bay‐margin and fluvio‐tidal brackish‐water channels. The two oldest parasequences comprise dominantly tide‐dominated, wave‐influenced/fluvial‐influenced, shoreface to bay‐margin deposits bisected by penecontemporaneous brackish‐water channels. Brackish‐water channels trend approximately north‐west/south‐east, which is perpendicular to the interpreted shoreline trend; this implies that the basinward and progradational direction was towards the north‐west during deposition of the upper McMurray Formation in Grouse Paleovalley. The youngest parasequence is interpreted as amalgamated wave‐dominated/storm‐dominated delta lobes. The transition from tide‐dominated deposition in the oldest two parasequences to wave‐dominated deposition in the youngest is attributed mainly to drowning of carbonate highlands to the north and north‐west of the study area, and potentially to relative changes in accommodation space and deposition rate. The sedimentological, ichnological and regional distribution of the three facies associations within each parasequence are compared to modern and Holocene analogues that have experienced similar shifts in process dominance. Through this comparison it is possible to consider how shifts in depositional processes are expressed in the rock record. In particular, this study provides one of few ancient examples of preservation of depositional process shifts and showcases how topography impacts the character and architecture of marginal‐marine systems.